Outcome measures evaluating physical functioning and their measurement properties in adolescent idiopathic scoliosis: a protocol for a systematic review - Alison Rushton; Nicola R Heneghan; Deborah Falla; Samia Alamrani; Adrian Gardner (BMJ Open)
Introduction Physical functioning (PF) is the ability to carry out the physical activity of daily living. It is an important outcome that provides a meaningful evaluation of individuals’ life. PF can be assessed using patient-reported outcome measures, performance-based outcome measures or body structure and function measure. Measures need to be valid, reliable and responsive to change to evaluate the effects of an intervention. Adolescent idiopathic scoliosis (AIS) is the most common deformity among the paediatric population and impacts on individuals’ lives. This systematic review will appraise evidence on the measurement properties of PF tools in individuals with AIS.Methods/analysis A protocol for systematic review and meta-analysis informed by Cochrane guidelines is reported in line with Preferred Reporting Items for Systematic Reviews and Meta-Analysis-P. MEDLINE, PsycINFO, EMBASE, CINAHL, SPORTdiscus, Web of Science and PubMed will be searched in two stages, from inception until December 2019. Search 1 will inventory all studies that assessed PF in participants with AIS, without any limitations. The search terms will be scoliosis, adolescent and PF-related terms. Search 2 will include studies which investigated instrument measurement properties in the same population for measures identified in search one. Two reviewers will independently perform study selection, data extraction, risk of bias and overall quality assessment. The COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) risk of bias and a modified Grading of Recommendations, Assessment, Development and Evaluation (GRADE) guidelines will be used. A meta-analysis will be conducted if possible, or the evidence will be synthesised and summarised per measurement property per outcome measure per measurement type.Ethics and dissemination This review will provide recommendations for practice and future research, considering psychometric properties of outcome measures of PF in AIS. The results of this study will be disseminated through a peer-reviewed publication and conference presentation.PROSPERO registration number CRD42019142335.